2019
DOI: 10.1158/1078-0432.ccr-18-3275
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting of BCL2 with Venetoclax and MCL1 with S63845 Is Synthetically Lethal In Vivo in Relapsed Mantle Cell Lymphoma

Abstract: Purpose: Mantle cell lymphoma (MCL) is an aggressive subtype of B-cell non-Hodgkin lymphomas characterized by (over)expression of BCL2. A BCL2-targeting drug, venetoclax, has promising anticancer activity in MCL. We analyzed molecular mechanisms of venetoclax resistance in MCL cells and tested strategies to overcome it. Experimental Design: We confirmed key roles of proapoptotic proteins BIM and NOXA in mediating venetoclaxinduced cell death in MCL. Both BIM and NOXA are, however, differentially expressed in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 41 publications
3
47
1
Order By: Relevance
“…The key role of pro-apoptotic protein BIM in the pathogenesis of MCL has been proposed in a transgenic mouse model, when cyclin D1-transgenic mice harboring BIM-deficient B cells developed lymphomas with histopathologic and molecular features of human MCL [57]. Although approximately one-third of currently available MCL cell lines harbor mono-or biallelic BIM/BCL2L11 deletion, we have shown that this alteration is rarely found in patients with newly diagnosed MCL [58]. Even though a complete lack of BIM protein expression as a result of gene deletion is probably rare, the level of BIM protein expression was shown to negatively correlate with prognosis in MCL [59].…”
Section: Deregulation Of Bcl-2 Proteins In B-cell Non-hodgkin Lymphomasmentioning
confidence: 68%
“…The key role of pro-apoptotic protein BIM in the pathogenesis of MCL has been proposed in a transgenic mouse model, when cyclin D1-transgenic mice harboring BIM-deficient B cells developed lymphomas with histopathologic and molecular features of human MCL [57]. Although approximately one-third of currently available MCL cell lines harbor mono-or biallelic BIM/BCL2L11 deletion, we have shown that this alteration is rarely found in patients with newly diagnosed MCL [58]. Even though a complete lack of BIM protein expression as a result of gene deletion is probably rare, the level of BIM protein expression was shown to negatively correlate with prognosis in MCL [59].…”
Section: Deregulation Of Bcl-2 Proteins In B-cell Non-hodgkin Lymphomasmentioning
confidence: 68%
“…It is notable that the addiction to MCL-1 of primary cells from MM patients at relapse is increased compared to those at diagnosis [57]. Furthermore, preclinical studies have demonstrated the rationale to combine venetoclax and BH3 mimetic targeting MCL-1 in MCL and MM [69,70].…”
Section: Bh3 Mimetics Targeting Mcl-1mentioning
confidence: 99%
“…Venetoclax belongs to BCL2 homology 3 (BH3) mimetics that trigger cancer cell apoptosis by displacing proapoptotic BCL2 proteins, including BIM from the anti-apoptotic BCL2 protein (Figure 8). We and others have demonstrated that the MCL1/NOXA complex plays a pivotal role in mediating acquired venetoclax resistance in MCL, and that such a resistance can be overcome by concurrent therapy with the MCL1 inhibitor S63845 [106,143,144]. The disruption of other BCL2 family members, including the upregulation of BCL-XL, loss of BIM, or mutation of BAX were all associated with acquired venetoclax resistance [145][146][147].…”
Section: Resistance To Venetoclaxmentioning
confidence: 89%
“…We have demonstrated that BCL2-negative DLBCL that do not express the BCL2 protein by standard immunohistochemistry rely on MCL1 expression for survival [105]. Moreover, the combined inhibition of BCL2 and MCL1 led to synthetic lethality both in DLBCL and MCL [105,106]. In addition to BCL2 and MCL1, disruption of other key players or regulators of apoptotic pathways have been associated with poor clinical outcome (e.g., BCL-XL, BIM, and BIRC3) [69].…”
Section: Dna Damage Response and Disruption Of Mitochondrial Apoptosismentioning
confidence: 96%